2016
DOI: 10.1248/bpb.b16-00080
|View full text |Cite
|
Sign up to set email alerts
|

Radiosensitizing Effect of TRPV1 Channel Inhibitors in Cancer Cells

Abstract: Radiosensitizers are used in cancer therapy to increase the γ-irradiation susceptibility of cancer cells, including radioresistant hypoxic cancer cells within solid tumors, so that radiotherapy can be applied at doses sufficiently low to minimize damage to adjacent normal tissues. Radiation-induced DNA damage is repaired by multiple repair systems, and therefore these systems are potential targets for radiosensitizers. We recently reported that the transient receptor potential vanilloid type 1 (TRPV1) channel … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 43 publications
(46 reference statements)
0
19
1
Order By: Relevance
“…Considering the cell cycle arrest in irradiated cells, the cell proliferation could be decreased in irradiated cells. Cellular DNA damages are usually repaired in a few hours, 46,47) but in this study DNA damage response and repair factors were still not disappeared at 48 h after γ-irradiation. Previously, a phenomenon called senescencelike growth arrest (SLGA) was reported as a growth arrest reaction induced by radiation, 48) in which ATM and γH2AX were continuously activated.…”
Section: -23)contrasting
confidence: 55%
“…Considering the cell cycle arrest in irradiated cells, the cell proliferation could be decreased in irradiated cells. Cellular DNA damages are usually repaired in a few hours, 46,47) but in this study DNA damage response and repair factors were still not disappeared at 48 h after γ-irradiation. Previously, a phenomenon called senescencelike growth arrest (SLGA) was reported as a growth arrest reaction induced by radiation, 48) in which ATM and γH2AX were continuously activated.…”
Section: -23)contrasting
confidence: 55%
“…These results are consistent with the γ-irradiation-induced decrease of cell viability due to irreversible cell damage. 36) Based on the results in Fig. 1A, we chose a dose of 2.0 Gy for subsequent experiments using A549 cells.…”
Section: γ-Irradiation Induces Increased Motility Of A549 Cellsmentioning
confidence: 99%
“…[47][48][49][50][51] In addition, we have recently reported that a TRPV1 channel inhibitor suppressed DNA repair after irradiation, 32) suggesting that TRPV1 inhibitors might increase the radiosensitivity of cancer cells. 36) Therefore, administration of TRPV channel inhibitors concomitantly with radiotherapy might reduce the risk of metastasis, as well as amplifying the cytotoxic effect of radiation.…”
Section: Fig 4 Effect Of Trpv1 and Trpv4 Channel Inhibitors On γ-Irmentioning
confidence: 99%
“…Capsazepine was also found to be an inhibitor of Janus kinase/STAT3 signaling in prostate cancer cells (Huang et al, 2006). Capsazepine also sensitized A549 lung cancer cells to radiation therapy (Nishino et al, 2016). Thomas et al (2007Thomas et al ( , 2011Thomas et al ( , 2012 synthesized the capsaicin analog nonivamide (Fig.…”
Section: Antineoplastic Activity Of Synthetic Capsaicin Analogsmentioning
confidence: 99%